2019
DOI: 10.1108/ijcma-05-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of contractual governance on task and relationship conflict in inter-organisational transactions

Abstract: Purpose This paper aims to explain how contractual complexity, including contractual control, coordination and adaptation, makes a difference to the task and relationship conflict, and then, to investigate the moderating roles played by both, total interdependence and interdependence asymmetry, in altering the association between the two types of conflicts. Design/methodology/approach This study obtained data through a questionnaire survey in the Chinese construction industry and the final sample consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 87 publications
(114 reference statements)
2
22
0
Order By: Relevance
“…However, some reviews have revealed that existing empirical findings on conflict–performance relationships are in fact mixed and inconsistent (Mulki et al , 2015; Humphrey et al , 2017; De Clercq and Belausteguigoitia, 2017). While some scholars have investigated conflict as a unidimensional construct (Currie et al , 2017), others have decomposed it into relationship and task conflicts (Shaukat et al , 2017; Jimmieson et al , 2017; You et al , 2019). The literature shows that relationship conflict can damage employee perceived job performance, whereas the influence of task conflict on perceived job performance can be negative (Mulki et al , 2015; De Clercq and Belausteguigoitia, 2017) or positive (Todorova et al , 2013; Bai et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, some reviews have revealed that existing empirical findings on conflict–performance relationships are in fact mixed and inconsistent (Mulki et al , 2015; Humphrey et al , 2017; De Clercq and Belausteguigoitia, 2017). While some scholars have investigated conflict as a unidimensional construct (Currie et al , 2017), others have decomposed it into relationship and task conflicts (Shaukat et al , 2017; Jimmieson et al , 2017; You et al , 2019). The literature shows that relationship conflict can damage employee perceived job performance, whereas the influence of task conflict on perceived job performance can be negative (Mulki et al , 2015; De Clercq and Belausteguigoitia, 2017) or positive (Todorova et al , 2013; Bai et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2.1 Inter-organizational conflicts and their resolution in transition economies A vibrant study field as it is, conflict management theories aim at explaining and analyzing different levels of conflicts, including individual level, group and team level, organizational level and country level (Caputo et al, 2019;Posthuma, 2005). Although majority of the ongoing discussions primarily focus on individual and team-level conflicts (Posthuma et al, 2011;Peng and Tjosvold, 2011), some recent studies have shifted their attention to more macro unit issues, for example, inter-organizational conflict and its resolutions (Ade, 2019;You et al, 2019;Cheng et al, 2018;Wong et al, 2016). Inter-organizational conflict is defined as a process that starts when a party perceives differences and opposition with another party on interests, resources, practices, beliefs and values or whatever matters to both sides (Ma et al, 2017).…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Inter-organizational conflict is defined as a process that starts when a party perceives differences and opposition with another party on interests, resources, practices, beliefs and values or whatever matters to both sides (Ma et al, 2017). It is also believed that inter-organizational conflicts often lead to increased IJCMA 31,3 transaction costs (You et al, 2019), thus threaten focal organizations' survival and development.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Xu et al (2018) concluded that contractual risk allocation significantly influences the trust relationship between owners and contractors. The scholars argued that detailed contracts benefit effective communication and conflict resolution (You et al, 2019). These studies are inadequate as they do not consider contextual factors, especially the external environment.…”
Section: Introductionmentioning
confidence: 99%
“…The latest research argued that contract terms have multiple functions: contractual control, coordination, and adaptation (W. Wang et al, 2018). This classification provides a holistic perspective for understanding interorganizational contracts (W. Wang et al, 2018) and is supported by some researches (Gao et al, 2018;Wang, Lu, & Fang, 2019;You et al, 2019). However, this perspective is still scarce in the existing literature.…”
Section: Introductionmentioning
confidence: 99%